Analisis Kemampuan Pemecahan Masalah Siswa Dalam Mengerjakan Soal Matematika Model TIMSS Kelas IV MI Al-Huda Pungangan-Subang - Latifah, Lena (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This study aims to analyze the problem-solving abilities of students class IV MI in working on the TIMSS Model Mathematics problem. This research method uses descriptive qualitative method, where the research sample is 3 students class IV MI AL-HUDA Pungangan – Subang. And data collection uses several stages, including making data collection, data reduction, data presentation and drawing conclusions to obtain results as the original goal, namely knowing the problem solving abilities of grade IV students in solving math problems with the TIMSS Model. The results of this study indicate that the students' problem solving abilities are quite good even though there are one in 3 subjects who do not have good problem solving skills.